The Large-Scale Structure of the Universe - Peebles, P. J. E. (Phillip James Edwin) (Princeton series in physics., 2020)
The classic account of the structure and evolution of the early universe from Nobel Prize-winning physicist P. J. E. PeeblesAn instant landmark on its publication, The Large-Scale Structure of the Universe remains the essential introduction to this vital area of research. Written by one of the world's most esteemed theoretical cosmologists, it provides an invaluable historical introduction to the subject, and an enduring overview of key methods, statistical measures, and techniques for dealing with cosmic evolution. With characteristic clarity and insight, P. J. E. Peebles focuses on the largest known structures--galaxy clusters--weighing the empirical evidence of the nature of the clustering and the theories of how the clustering evolves in an expanding universe. A must-have reference for students and researchers alike, this edition of The Large-Scale Structure of the Universe introduces a new generation of readers to a classic text in modern cosmology.